2018
DOI: 10.1016/j.ccell.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Sequencing Defines the Genomic Landscape of Metastatic Colorectal Cancer

Abstract: Metastatic colorectal cancers (mCRCs) are clinically heterogeneous, but the genomic basis of this variability remains poorly understood. We performed prospective targeted sequencing of 1,134 CRCs. We identified splice alterations in intronic regions of APC and large in-frame deletions in CTNNB1, increasing oncogenic WNT pathway alterations to 96% of CRCs. Right-sided primary site in microsatellite stable mCRC was associated with shorter survival, older age at diagnosis, increased mutations, and enrichment of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

50
644
8
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 655 publications
(748 citation statements)
references
References 35 publications
50
644
8
5
Order By: Relevance
“…The use of a blood samples collected at different time points also precluded appropriate comparison of RAS mutational status between tissue and plasma, and single‐point blood sampling makes it impossible to analyze time‐course change in ctDNA during chemotherapies, which could be more useful information to assess the chemotherapeutic response. Moreover, the frequencies of mutated genes in plasma ctDNA of patients with CRC in our study were inconsistent with those in tissue DNA which had been reported in mutation database including The Cancer Genome Atlas . Although the mutation frequency of APC gene in CRC tissue has been reported to be ~80%, it revealed only 23.7% in our data (plasma), which was significantly lower frequency than that in tissue.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…The use of a blood samples collected at different time points also precluded appropriate comparison of RAS mutational status between tissue and plasma, and single‐point blood sampling makes it impossible to analyze time‐course change in ctDNA during chemotherapies, which could be more useful information to assess the chemotherapeutic response. Moreover, the frequencies of mutated genes in plasma ctDNA of patients with CRC in our study were inconsistent with those in tissue DNA which had been reported in mutation database including The Cancer Genome Atlas . Although the mutation frequency of APC gene in CRC tissue has been reported to be ~80%, it revealed only 23.7% in our data (plasma), which was significantly lower frequency than that in tissue.…”
Section: Discussioncontrasting
confidence: 98%
“…Moreover, the frequencies of mutated genes in plasma ctDNA of patients with CRC in our study were inconsistent with those in tissue DNA which had been reported in mutation database including The Cancer Genome Atlas. 53,54 Although the mutation frequency of APC gene in CRC tissue has been reported to be ~80%, 53,55 it revealed only 23.7% in our data (plasma), which was significantly lower frequency than that in tissue. The difference of the above frequencies could be partially explained by insufficient coverage of mutation detection in APC gene of the panel used in our ctDNA study.…”
Section: Discussionmentioning
confidence: 51%
“…APC inactivating mutations lead to aberrant activation of Wnt signaling via β‐catenin stabilization and KRAS mutations result in uncontrolled ERK signaling . It was reported that around 80%–96% of human CRCs involve APC mutation and half of CRCs contain activating mutations in KRAS , highlighting the dominating roles of Wnt and ERK signaling in the development of CRC . In addition to APC , several mutations in β‐catenin, Axin, and GSK3 genes in Wnt pathway also cause significantly deregulated nuclear β‐catenin accumulation, aberrant cell proliferation, and malignant transformation in the colon epithelium …”
Section: Introductionmentioning
confidence: 99%
“…Generally, somatic mutations of TGF‐beta signaling‐related genes are reported to contribute to unresponsiveness to TGF‐beta‐induced EMT . In particular, SMAD4 mutation occurs in 32% of pancreatic cancer, 16% of non‐hyper‐mutated colorectal cancer and 8% of non‐hyper‐mutated gastric cancer patients . Dominant negative mutation of SMAD2 , SMAD3 and SMAD4 resulted in unresponsiveness to TGF‐beta‐induced EMT through disruption of canonical SMAD‐mediated TGF‐beta signaling, although EMT can be induced in control cells by TGF‐beta stimulation .…”
Section: Discussionmentioning
confidence: 99%